2014
DOI: 10.2169/internalmedicine.53.0698
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Refractory Gout Using Combined Therapy Consisting of Febuxostat and Allopurinol in a Patient with Chronic Renal Failure

Abstract: Gouty arthritis is a metabolic disorder associated with hyperuricemia. Despite the development of novel pharmacotherapies, some hyperuricemia patients are drug refractory and develop gout. A 74-year-old man with frequent gouty attacks and chronic renal failure presented with asymmetrical polyarthritis affecting multiple joints. The diagnosis of gout was confirmed based on the presence of monosodium urate crystals in the patient's right wrist. The administration of systemic corticosteroids relieved the joint in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Using the search terms as outlined in Supplementary Table 1, 1678 studies of glucocorticoid use were initially identified, as summarised in a PRISMA flowchart summary (Supplementary Figure 4). After a sequential review of the title, abstract and full-text, a final total of 12 studies were included for data extraction [57,64,[87][88][89][90][91][92][93][94][95][96]. Eleven out of these 12 studies were of case reports (n = 10) and of case series (n = 1) [57,[87][88][89][90][91][92][93][94][95][96].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Using the search terms as outlined in Supplementary Table 1, 1678 studies of glucocorticoid use were initially identified, as summarised in a PRISMA flowchart summary (Supplementary Figure 4). After a sequential review of the title, abstract and full-text, a final total of 12 studies were included for data extraction [57,64,[87][88][89][90][91][92][93][94][95][96]. Eleven out of these 12 studies were of case reports (n = 10) and of case series (n = 1) [57,[87][88][89][90][91][92][93][94][95][96].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Hatoum et al ( 27 ) examined a database of adults with newly diagnosed gout and concluded that febuxostat was effective in the management of gout. Maekawa et al ( 28 ) reported that allopurinol, febuxostat, and benzbromarone therapy reduced serum urate levels to below 6 mg/dL in the treatment of refractory gout. Huang et al ( 29 ) reported that the urate-lowering efficacy of febuxostat at 80 mg QD was greater than that of febuxostat at 40 mg QD and allopurinol at 300 mg QD.…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing and comparable in vitro experiments were not performed in any of the previous studies. Studies of molybdenum cofactor deficiency (MoCD) made use of knockout mice to study the molecular basis and treatment of human MoCD [26,27]. To confirm our hypothesis, we next intend to establish animal models, namely homozygous MCSU −/− and heterozygous MCSU −/+ mice.…”
Section: In Vitro Study Quantitative Rt-pcr Examination Of the Mcsu Imentioning
confidence: 99%